Development of Learning Models Using Picture Paper Media in Improving Indonesian Language Ability in Grade V Elementary School 028 Lumban Dolok Siabu - Sutikno; Ainun, Nur (PT Inovasi Pratama Internasional, 2025)
The problem solved through this research is the speaking difficulties of fifth-grade students at SD Negeri 028 Lumban Dolok in the 2024-2025 academic year in expressing ideas in a formal or official atmosphere. The method used in this research was a qualitative approach with a classroom action research design. The reason for using this method and design is that the research data are in qualitative form and are conducted in a classroom context. The aim of this action research is to improve the conditions of professional learning practices in the classroom. The subjects in this research were 17 class V students of SD Negeri 028 Lumban Dolok for the 2024-2025 academic year, consisting of nine men and eight women. The results of actions in learning to speak using image media are very effective for mastering the areas of vocabulary, language structure, the relationship between topics and content, content structure, courage, and students' speaking fluency. Based on the results of the actions from cycles I to III, the increase was between 20% and 40%. Finally, the use of image media in learning can be performed in two ways: selecting images as materials and methods as tools. There are techniques for using media that are attached to and given to students. The selection of images was adjusted according to the student's character, and four images were sufficient. Even though the use of images has been quite successful, there are still obstacles. The obstacle experienced by students is that if they are asked to use good and correct Indonesians in telling stories, they still lack mastery